Increased Neuronal Differentiation of Neural Progenitor Cells Derived from Phosphovimentin-Deficient Mice - Chen, Meng (Mol Neurobiol, 2017)
Vimentin is an intermediate filament (also known as nanofilament) protein expressed in several cell types of the central nervous system, including astrocytes and neural stem/progenitor cells. Mutation of the vimentin serine sites that are phosphorylated during mitosis (VIM (SA/SA)) leads to cytokinetic failures in fibroblasts and lens epithelial cells, resulting in chromosomal instability and increased expression of cell senescence markers. In this study, we investigated morphology, proliferative capacity, and motility of VIM (SA/SA) astrocytes, and their effect on the differentiation of neural stem/progenitor cells. VIM (SA/SA) astrocytes expressed less vimentin and more GFAP but showed a well-developed intermediate filament network, exhibited normal cell morphology, proliferation, and motility in an in vitro wound closing assay. Interestingly, we found a two- to fourfold increased neuronal differentiation of VIM (SA/SA) neurosphere cells, both in a standard 2D and in Bioactive3D cell culture systems, and determined that this effect was neurosphere cell autonomous and not dependent on cocultured astrocytes. Using BrdU in vivo labeling to assess neural stem/progenitor cell proliferation and differentiation in the hippocampus of adult mice, one of the two major adult neurogenic regions, we found a modest increase (by 8%) in the fraction of newly born and surviving neurons. Thus, mutation of the serine sites phosphorylated in vimentin during mitosis alters intermediate filament protein expression but has no effect on astrocyte morphology or proliferation, and leads to increased neuronal differentiation of neural progenitor cells.